ENHANCING ENGLISH LITERACY THROUGH SITUATED PRACTICE OF MULTILITERACIES PEDAGOGY: A MIXED-METHOD STUDY AT SMPN NEONBAT - Mikhael Misa; Hesni Neno (University of Kuningan, 2026)
This study investigates the Situated Practice of Multiliteracies Pedagogy in enhancing students' English literacy at SMPN Neonbat, a rural Indonesian school. The research employs a mixed-methods approach that integrates quantitative and qualitative data, as outlined in the multiliteracies framework, which emphasizes learning through multiple modalities and socio-cultural contexts. Pre- and post-test assessments were administered to collect quantitative data on reading comprehension and grammar. Conversely, qualitative data were collected through student interviews and classroom observations to investigate perceptions and engagement. The results indicate that students' performance has significantly improved in all areas. There was a substantial increase in reading comprehension scores, with gains of 95% in objective questions, 85% in fill-in-the-blank, and 74% in matching exercises. The improvement in grammar scores was even more significant, with a total of 133%, 121%, and 108%, respectively. The significance of these gains was verified through statistical analysis utilizing paired-sample t-tests. Qualitative research demonstrated that students were more engaged, confident, and actively involved in the learning process, particularly when courses were aligned with their cultural and social backgrounds. In general, the research indicates that the Situated Practice of Multiliteracies Pedagogy is effective in improving English literacy. It is particularly well-suited for rural educational environments due to its emphasis on contextualized, collaborative, and meaningful learning.